Tea Collector: Web Based Data Tracking Solution for Tea Smallholders - Bandara, Avishka; Epitakaduwa E.K.G.D; Basnayaka A.I; Wijewardena O.K; D. I. De Silva; S. M. D. T. H. Dias (International Journal of Engineering and Management Research, 2022)
The sustainability of a tea factory also depends on the trustworthiness of the data collection and finance management. Collection of tea leaves and tea processing are the main two processes done by a tea factory. In the process of tea collection, they must handle a large set of data about the tea collection, selling, and payments. Data processing and summarizing can be identified as critical process because these summarizations finally sent to the factory for further analyzes. All these documentation processes are still handled mostly in a manual way. This manual process may lead to malpractices sometimes, especially when handling payments. So, there is a need to develop an easy way to manage all the documentation processes online. In this specific research, our idea is to implement a web application with features like adding, updating, and deleting data with a generation of summary reports. The main reason we need to shift from a normal manual process to an online managed process is that they can consume their time by managing the data more secure and trustworthy way. We have implemented this by using MERN stack as the technology where we use react.js for the frontend and express.js for the backend developments. We used MongoDB as the database and Heroku to host the application.